Executives and Smartphones: An ambiguous and paradoxical relationship. - Gonçalves, Ana Paula Borges; Joia, Luiz Antonio (Organizações & Sociedade, 2014)
Based on theoretical approaches concerning the existence of paradoxes associated with the use of technological appliances, this article seeks to identify the existence of ambiguities in the day-to-day use of smartphones by Brazilian executives. The single representative case study method was applied, by analysing a Brazilian company within the pharmaceutical sector, which has a policy of providing smartphones to its senior executives. Data were collected from: questionnaires filled out by fourteen executives of the company in question; in-depth interviews conducted with five of these executives and e-mails sent by them via smartphones over a given period of time. After consolidation and analysis of the data obtained, it was seen that two paradoxes were strongly related to the use of smartphones by the executives in question, namely: continuity vs. asynchronicity and autonomy vs. addiction. Furthermore, three other paradoxes were moderately associated with the use of smartphones by the executives in question, namely freedom vs. enslavement, dependence vs. independence, and planning vs. improvisation. Lastly, the implications and limitations of the research are set forth.